Functional and conformational changes in the aspartic protease cardosin A induced by TFE - Fraga, Ana Sofia (2019)
Conformational and functional changes of cardosin A, an aspartic protease of vegetal origin, in the presence of 2,2,2-trifluoroethanol (TFE), were assessed. TFE induced alterations of cardosin activity and conformation that differed with the solvent concentration. MD simulations showed that there are significant local alterations in protein flexibility and TFE molecules were found to replace several hydration molecules in the active site of the enzyme. This may explain some of the activity loss observed in the presence of TFE, especially at low TFE concentrations, as well as the recovery of enzyme activity upon aqueous dilution, indicating the release of the TFE molecules from the active site.